Improvement in liver function and gross motor function after umbilical cord-derived mesenchymal stromal cell transplantation in a child with autoimmune hepatitis and concurrent cerebral palsy: a case report - Liem Thanh Nguyen; Huong Thu Le; Doan Van Ngo; Thi Kieu Trang Phan (Frontiers in Medicine, 2026)
Autoimmune hepatitis (AIH) is a complex immune-mediated liver disease of unknown origin that can rapidly progress to liver cirrhosis and end-stage liver failure. Standard treatment regimens typically involve immunosuppressive therapies, with most patients requiring lifelong maintenance. Recently, cell therapy has emerged as a potential therapeutic option for AIH. In this study, we report the case of a 2-year-old boy with type 2 autoimmune hepatitis and postcardiac arrest cerebral palsy who experienced clinical and biochemical improvement following umbilical cord-derived mesenchymal stromal cell (UC-MSC) infusion. Six months after the cell infusion, liver enzyme levels markedly reduced and remained stable throughout the 1-year follow-up period. At 1 year post-infusion, the patient demonstrated significant improvements in motor function, language skill, along with reduced hypertonia. At the most recent follow-up, his liver enzyme levels were within the normal range, and he had made substantial progress toward achieving developmental milestones. These clinical and biochemical changes suggest that UC-MSC therapy has potential as an adjunctive therapeutic approach. However, because this is a single, uncontrolled observation with several concurrent confounders, the clinical efficacy of UC-MSC therapy cannot be established from this case alone. Larger-scale studies with appropriate control groups, longer follow-up periods, and more detailed mechanistic assessments are required to determine whether UC-MSC therapy provides a true therapeutic benefit. No infusion-related adverse events were observed during follow-up.